Kazimierz Twardowski’s Philosophy and Mykhailo Rudnytskyi’s Literary Criticism - Honcharenko, Olha (Ruch Filozoficzny, 2021)
In this article Twardowski’s philosophy and Rudnytskyi’s literary criticism have been compared for the first time. The purpose of the comparative analysis was to identify Twardowski’s tradition in the works of his student Rudnytskyi. This comparison seems to contribute to a rethinking of Rudnytskyi’s literary criticism in Ukrainian culture, namely to clarify its philosophical background, conceptual apparatus, and methodology. In the introduction some critical remarks on Rudnytskyi’s literary work, that were made by Ukrainian scholars, have been provided. Next, in the first part, the methodological and philosophical background of Twardowski’s philosophy has been analyzed. The second part encompasses an attempt to reconstruct Rudnytskyi’s literary criticism. In the third part the author argues the direct impact of Twardowski’s philosophy on Rudnytskyi’s literary criticism. Finally, in the conclusions, the author claims that Rudnytskyi’s literary criticism had a philosophical background, conceptual apparatus, and methodology.